Emergency Care Use and the Medicare Hospice Benefit for Individuals with Cancer with a Poor Prognosis. Issue 2 (25th January 2016) - Obermeyer, Ziad; Clarke, Alissa C.; Makar, Maggie; Schuur, Jeremiah D.; Cutler, David M.
Abstract : Objectives: To compare patterns of emergency department (ED) use and inpatient admission rates for elderly adults with cancer with a poor prognosis who enrolled in hospice to those of similar individuals who did not. Design: Matched case–control study. Setting: Nationally representative sample of Medicare fee‐for‐service beneficiaries with cancer with a poor prognosis who died in 2011. Participants: Beneficiaries in hospice matched to individuals not in hospice on time from diagnosis of cancer with a poor prognosis to death, region, age, and sex. Measurements: Comparison of ED use and inpatient admission rates before and after hospice enrollment for beneficiaries in hospice and controls. Results: Of 272, 832 matched beneficiaries, 81% visited the ED in the last 6 months of life. At baseline, daily ED use and admission rates were not significantly different between beneficiaries in and not in hospice. By the week before death, nonhospice controls averaged 69.6 ED visits/1, 000 beneficiary‐days, versus 7.6 for beneficiaries in hospice (rate ratio (RR) = 9.7, 95% confidence interval (CI) = 9.3–10.0). Inpatient admission rates in the last week of life were 63% for nonhospice controls and 42% for beneficiaries in hospice (RR = 1.51, 95% CI = 1.45–1.57). Of all beneficiaries in hospice, 28% enrolled during inpatient stays originating in EDs; they accounted for 35.7% (95% CI = 35.4–36.0%) of all hospice stays of less than 1 month and 13.9% (95% CI = 13.6–14.2%) of stays longer than 1 month. Conclusion: Most Medicare beneficiaries with cancer with a poor prognosis visited EDs at the end of life. Hospice enrollment was associated with lower ED use and admission rates. Many individuals enrolled in hospice during inpatient stays that followed ED visits, a phenomenon linked to shorter hospice stays. These findings must be interpreted carefully given potential unmeasured confounders in matching.